Glutamate dehydrogenase isoenzyme 3 (GDH3) of Arabidopsis thaliana is regulated by a combined effect of nitrogen and cytokinin - Marchi, Laura (Plant physiology and biochemistry : PPB, 2013)
Copyright © 2013 Elsevier Masson SAS. All rights reserved.